Integration of Forest Management Policy and Environmental Law Enforcement in Efforts to Prevent Illegal Logging in Indonesia - Ahmad Syahird; Samsul Arifin; Andi Firmansyah; Andi Muhammad Alqadri Syarif (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2026)
Law enforcement against illegal logging in various forest areas in Indonesia remains a persistent challenge in achieving sustainable forest governance. Although Indonesia has enacted Law No. 18 of 2013 concerning the Prevention and Eradication of Forest Destruction, prior studies largely focus on regulatory substance and criminalization, while limited attention has been given to the structural effectiveness of its enforcement mechanisms. This study aims to analyze the effectiveness of environmental law enforcement in preventing illegal logging and to identify the institutional and normative gaps that hinder its implementation. This research employs normative juridical legal research with a statutory, conceptual, and case approach. The analysis is based on legislation, court decisions related to illegal logging, and relevant scholarly literature to evaluate the coherence between regulatory design and enforcement practice. The findings indicate that despite a relatively comprehensive legal framework, enforcement remains suboptimal due to fragmented inter-agency coordination, limited institutional capacity, and systemic corruption risks within forestry governance. Moreover, the existing regulatory framework has not been fully supported by integrated monitoring and accountability mechanisms. This study contributes to the discourse on environmental law enforcement by proposing the strengthening of cross-sectoral supervision, institutional integration, and community-based monitoring as key reform directions for improving the effectiveness of illegal logging prevention in Indonesia.